Thermal analysis of a vertically based fin array in a bounded region : a numerical experiment - Lee, Lai Kin (2003)
This study uses finite volume method (QUICK) to simulate the natural convection heat transfer of a vertically based fin array where each of the surfaces are isothermal for different aspect ratios and different angles of the base surface. A computer programme is developed to solve the problem by applying continuity equation, momentum equation and energy equation. The velocity contour and the temperature contour for different aspect ratios and different angles of the base surface will be observed. Based on the Nusselt number and Rayleigh Number that will be calculated, a natural convection correlation equation of a vertically based fin array is derived. The accuracy of the developed correlation will be compared with the correlation obtained from literature.